Cost of doing business during COVID-19: SME investment in public health compliance - Janez Kren; Martina Lawless; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2021)
In this paper, we use a novel survey module to consider investment in health-related expenditures by SMEs following the onset of the COVID-19 pandemic in Ireland. Using a unique dataset designed to capture expenditure on public health measures, we explore the heterogeneity in expenditure across firms and explore its determinants using traditional models. We find that 86 per cent of SMEs invested in health measures with a mean investment of =C15,500 and a median of =C3,500. Nearly all investment was financed by internal funds. Health investments are uncorrelated with economic performance and financial factors, in contrast to traditional models of investments. This highlights the random nature of the COVID-19 shock.
Keywords: D22; 330; SMEs; investment; financing; COVID-19; public health measures